Validity of the Mental Health Continuum – Short Form among home-language Setswana speaking South Africans: evidence for a four-factor model - Opperman, Ingrid; Potgieter, Johan C.; Daniel-Smit, Jessica (Frontiers in Psychology, 2025)
From a positive psychology perspective, it has been proposed that mental health comprises three dimensions: emotional well-being (EWB), psychological [or personal] well-being (PWB), and social well-being (SWB). To assess these dimensions, Keyes (2002) developed the Mental Health Continuum – Short Form (MHC-SF), which has been validated in various cultural contexts. In this model, mental health is operationalized as the presence of various positive indicators rather than the absence of psychopathology in a model which is purported to be cross-culturally applicable. While numerous studies support the original, correlated three-factor model, some current arguments are being made for a bifactor model with three dimensions. However, few newer validation studies explore the possibility of alternate models which might be applicable to non-Western, collectivist cultures who can also benefit from accurate assessments and positive psychology interventions. This study assessed the validity of the MHC-SF among 308 Setswana home-language South Africans aged 19–31 years. Results indicated that the correlated three-factor structure or bifactor model validated previously was a good fit, but a correlated four-factor model was a better fit and a bifactor model with four dimensions was the best fitting. An initial exploratory factor analysis using maximum likelihood and promax rotation suggested that this was due to the social well-being scale being divisible into: “belonging in society” (social 1) and “perceptions of society” (social 2) rather than a single construct (social well-being). These results emphasize the distinct aspects of well-being in a Setswana-speaking sample, highlighting the importance of culturally and linguistically informed models of mental health, particularly in collectivistic cultures within developing countries. This has implications for the use of the MHC-SF in research and culturally appropriate assessment and intervention design, as well as the applicability of fundamental models of mental health in non-Western and African contexts.